AZHAR MAROOF RASHID-AMR Staging of Juvenile Angiofibroma: A New Staging System based on Anatomical Spread of the Disease – 25 Years Experience at Mayo Hospital, Lahore, Pakistan - MAROOF AZIZ KHAN, SALMAN AFTAB AHMED, AZHAR HAMEED, MUHAMMAD RASHID AWAN, (Journal of Fatima Jinnah Medical University, 2018)
Objective: The purpose of this study is to frame a simple method of staging the juvenile angiofibroma. A new staging system is introduced as Azhar Maroof Rashid -AMR staging based on the anatomical spread of the disease process in our past 25 years clinical experience. Study design: Retrospective study Place and duration of study: This study was conducted in department of ENT Unit 1, Mayo Hospital, Lahore associated with King Edward Medical college/University Lahore. It spanned over a period of 25 years from June 1988 to July 2012. Material and method: A total of 30 consecutive recorded patients with suspected juvenile angiofibroma were evaluated preoperatively by history, examination, plane radiology, contrast enhanced CT scan and four vessels subtraction angiography depending on the availability and indication. Patients with recurrent disease were also included in the study. Results: All patients were male. The average age of the patients was 16 years (SD 18.5±6.5). They ranged in age from 12 to 25 years. 6 (20 %) patients presented with recurrent disease. Conclusion: Intradural extension could not be demonstrated radiologically as well as peroperatively in our past 25 year’s experience. Therefore, in the new classification dural involvement was not taken into account.